PENGARUH MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA SMA - Yuhana Yuhana; Maridi Maridi; Sri Dwiastuti (Prosiding Seminar Nasional Lembaga Penelitian Dan Pendidikan (LPP) Mandala)
This research is to know the effect of biology-based inquiry learning to the improveof students critical thinking skillsin State Senior High School 1 Sembalun on academic year 2017/2018.The research was done in State Senior High School 1 Sembalun and sample on research is class X of IPA toward 29 students. Instrument use in this reseach was essay test. Based on research result show gotten a score of pretest average value is 61.66 and a score of critical thinking skills posttest is 80.86, while average value of gain is 0,51 with a middle category. The research can be concluded that biology-based inquiry learning influence improve of students critical thinking skill in class X of IPA.